How do the geometries of the broach handles relate to the distribution of force and moments in a femoral model?. (December 2020) - Fonseca Ulloa, Carlos A.; Seeger, Anja; Ishaque, Bernd A.; Ahmed, Gafar A.; Rickert, Markus; Jahnke, Alexander
Highlights: Minimally invasive surgery requires a change in the geometries of broach handles. Losses between force applied and force measured increase with degree of curvature. Moments losses are the lowest by straight handle and the highest by the double-curved. Handles should be modified so that unwanted forces or moments can be compensated. Abstract: The continuous improvement of minimally invasive hip endoprostheses surgery comes with a change in geometries of surgery instruments like the broach handles. Consequently, depending on the handles' curvature this results in a deviation between handle and femoral axis. Therefore, this study aimed to prove the influence of different handles' curvatures on the preparation of implant site and acting forces and moments in this process. Five femoral models attached to different handles (double-curved, single-curved, straight) were locked in a drop-weight device with standardize implantation forces and moments and five strokes were measured for each possible combination. Distribution of force and moment components was dependent on the handle's curvature, where the lowest variation from the standard force values was by the straight one (av:15.2% ± 0.5%) and the strongest discrepancies were exhibit by the double-curved one (av:54.3% ± 0.1%.). Moment values have also shown this trend with the lowest variation (12.4%–23.3%) by the straight one and the highest discrepancies (56, 6%-90.9%) by the double-curved one. Results show that unguided axial impact introduces unwanted transverse forces and moments into the femur. Therefore, broach handles should be modified accordingly so that minimally invasive surgery remains feasible but unwanted forces or moments can still be compensated.